A One Health systematic review and meta-analysis of Coxiella burnetii prevalence in humans, animals, and vectors in Algeria - Yousfi, Safia; Fares, Roufaida; Khelifi Touhami, Nadjet Amina; Salhi, Omar; Ouchene, Nassim (Veterinaria Italiana, 2026)
Coxiella burnetii, the causative agent of Q fever, is a globally distributed zoonotic pathogen affecting humans, domestic animals, and arthropod vectors. In Algeria, fragmented data suggest widespread circulation, yet no comprehensive quantitative assessment exists. This study aimed to systematically review and meta-analyse the prevalence of C. burnetii in humans, animals, and vectors in Algeria, using a One Health perspective. A systematic search of PubMed, Scopus, Web of Science, and Google Scholar was conducted up to January 2026. Studies reporting serological or molecular detection of C. burnetii in Algeria were included. Random-effects meta-analysis was performed to estimate pooled prevalence, with subgroup analyses by host species, region, and diagnostic method. A total of 35 studies were included, encompassing 8,372 samples and 80 prevalence observations. Pooled prevalence was highest in camels (73.7%; 95% CI: 66.5–79.8%), followed by small ruminants (15.8%; 95% CI: 10.6–22.9%) and cattle (11.8%; 95% CI: 7.2–18.8%). Ticks showed a pooled prevalence of 10.0% (95% CI: 3.2–27.1%), while human infection had a pooled prevalence of 3.7% (95% CI: 0.9–13.9%). The south-eastern region exhibited the highest prevalence, and serological methods generally reported higher rates than molecular methods. High heterogeneity (I² > 75%) was observed across studies. Coxiella burnetii is widely circulating among humans, domestic animals, camels, and ticks in Algeria, with notable variation between hosts and regions. Camels and small ruminants act as major reservoirs, while humans remain at risk, particularly those in close contact with livestock. Integrated One Health surveillance and targeted control strategies are urgently needed to reduce the burden of Q fever.